Bernd Alois Zimmerman Recomposed - Zimmermann, Bernd Alois 1918-1970; Holliger, Heinz 1939-; Westdeutscher Rundfunk (Cologne, Germany) (Mainz Wergo, 2022)
Bernd Alois Zimmermann (1918–1970) was one of the most distinctive composers in the musical avant-garde after the Second World War. While Karlheinz Stockhausen served as a kind of ‘generator’ in Cologne during the 1950s and 60s, inventing completely new sounds and techniques, Zimmermann was in many ways his opposite, a ‘transformer’ who redefined previously existing material by placing it in new contexts and collage-like structures, anticipating the ideas of the Postmodernists.Zimmermann created these new contexts on many levels. Especially in his younger years, he arranged and orchestrated songs and piano pieces using brash and daring instrumental colors. These arrangements then found their way into his works that are now recognized as modern masterpieces: “Alagoana”, “Konzert”, “Sinfonie in einem Satz”, “Stille und Umkehr”, etc. His self-composed works employing numerous quotations as well as his arrangements ‘recomposing’ previously existing music are juxtaposed in the excellent recordings presented by WERGO in this collection. It contains more than three hours of music as well as an extensive booklet with a wealth of information and an interview with Heinz Holliger, the guiding spirit behind this production. Holliger conducted all of the recordings and has worked for years to ensure that Zimmermann’s long-forgotten arrangements were rescued, published, performed, and recorded. The performances and recordings took place as part of the celebrations organized by the WDR in Cologne in honor of Zimmermann’s 100th birthday.This new release from WERGO presents a fresh perspective on the composer Bernd Alois Zimmermann, whose tragic suicide shortly after the completion of “Stille und Umkehr” shocked the musical world. His fascinating instrumental effects and his embrace of popular and traditional music make his works feel much more at home in our contemporary world than they did in the cultural atmosphere of his time, with its faith with technology and progress.
Original Compositions and Arrangements for Orchestra